Uptake of agroforestry-based crop management in the semi-arid Sahel – Analysis of joint decisions and adoption determinants - Grovermann, C.; Rees, C.; Beye, A.; Assfaw Wossen, T.; Abdoulaye, Tahirou; Cicek, H. (Frontiers Media, 2023)
Introduction: Agroforestry plays a vital role in maintaining and developing the resilience and productivity of farms and landscapes. Scientific evidence from the Sahel region suggests that integration of trees and shrubs has the potential to improve temperature and moisture levels whilst providing bio-based fertilizer that contributes to increased yields of annual crops. However, little is known about the factors that influence the di􀀀usion of agroforestry. This study examines joint decisions on the use of agroforestry alongside other complementary agricultural practices and disentangles agroforestry awareness fromadoption and disadoption decisions.